Effect of Vitamin D Supplementation on Insulin Resistance Status in Pubertal Girls with Congenital Adrenal Hyperplasia - Abdou, Marise; Hassan, Mona Mamdouh; ElAtti, Sahar Abd; Aiad, Diana Nabil; Ibrahim, Amany (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Congenital adrenal hyperplasia (CAH) patients especially females are at increased risk for developing obesity and resistance to insulin (IR). Rising evidence indicate that insufficient vitamin D levels are associated with impaired function of β-cells of islets of Langerhans and IR, however, this finding hasn’t been investigated in patients with CAH. The aim was to identify the vitamin D levels and insulin resistance status in pubertal females with CAH, following up at Diabetes Endocrine and Metabolism Pediatric Unit, Abou ElRish Children’s Hospital, Cairo University. We also examined the association between vitamin D level & insulin resistance and the impact of cholecalciferol administration on metabolic abnormalities. Subjects and Methods: Sixteen pubertal CAH females with deficient or insufficient Vitamin D levels were recruited. Follow up was done after a period of 6 months during which oral Vitamin D replacement therapy was prescribed. Results: The serum levels of 25-hydroxyvitamin D (25(OH)D3) were significantly raised following replacement therapy. Significant correlation was detected between HOMA-IR and serum levels of insulin, other IR indices both prior to and following vitamin D supplementation. However, HOMA-IR didn’t correlate with any of the following: 25(OH)D3 levels, 17 hydroxyprogesterone (17-OHP), or steroid dose either prior to or following replacement therapy. Conclusion: Vitamin D replacement therapy didn’t have favorable effects on IR in females with CAH. Future research using randomized controlled trials is required to examine the impact of Vitamin D on IR. This might influence the production of adrenal androgen, resulting in reduction of the therapeutic effect of glucocorticoids and evolution of metabolic derangements.